Public Oversight and Reporting Credibility: Evidence from the PCAOB Audit Inspection Regime - Gipper, Brandon; Leuz, Christian; Maffett, Mark (Review of Financial Studies, 2020)
Abstract This paper studies the impact of public audit oversight on financial reporting credibility. We analyze changes in market responses to earnings news after public audit oversight is introduced, exploiting that the regime onset depends on fiscal year-ends, auditors, and the rollout of auditor inspections. We find that investors respond more strongly to earnings news following public audit oversight. Corroborating these findings, we find an increase in volume responses to 10-K filings after the new regime. Our results show that public audit oversight can enhance reporting credibility and that this credibility is priced in capital markets. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.